Giant cell tumor arising from the anterior arc of the rib: an extremely rare site in an adolescent girl - Özyüksel, Gül; Ardıçlı, Burak; Özcan, H Nursun; Gedikoğlu, Gökhan; Varan, Ali; Karnak, İbrahim (The Turkish Journal of Pediatrics, 2022)
Background. Giant cell tumor is a rare and locally aggressive neoplasm of the long bones in children. Rib is the least frequently affected site, seen in less than 1% of all cases and most of them occur at the posterior arc. Case. A 12-year-old girl presented with swelling and slight pain on the left inferior-anterior chest wall for two years. Physical examination revealed a giant, hard and fixed mass on the left chest wall. Hematological and biochemical test results were in normal limits but slight elevation of alkaline phosphatase level. Computed tomography of the chest showed a large expansive mass and lytic lesion with internal calcification arising from the anterior part of the 7th rib. En-bloc resection was performed including the 6th-8th ribs and a small part of the diaphragm. The pathological evaluation revealed giant cell tumor of bone. Conclusions. Herein, we aim to emphasize that giant cell tumor should be considered in the differential diagnosis of chest wall tumors in childhood whereby en-bloc resection and close follow up would be paramount.
Keywords: chest wall tumor; child; costa; giant cell tumor; treatment